Marcher Castle on Fire. Aftermath of a 15th Century Siege - Marek, Lech (Institute of Archaeology and Ethnology of Polish Academy of Sciences, 2017)
Castle Kolno was set afire and put to ruin on the day of St. Margaret 1443 in the course of the so- called succession war in Silesia. The main purpose of this paper is to present the possible interpretation of selected pieces of archeological evidence for this dramatic event. Destruction layers documenting the siege contained mediaeval arms and armor – finds. The exchange of crossbow fire during the hostilities must have been tremendous as confirmed by the high number of bolt-finds. Moreover, there is evidence of the use of firearms in the conflict. On the basis of the most numerous militaria- finds recorded, such as projectiles, pieces of armor and riding gear, one can draw general conclusions on the character of 15th-century warfare. Much older objects related to the origins of the castle, its function as a border fortress guarding the ducal custom house, as well as those documenting the daily life of its inhabitants were also found in this context. The presented discussion aims to address the problem of chronological inconsistencies among the artifacts from the destruction layers. The objective of this paper is not a thorough analysis of particular artifacts, but a preliminary presentation of the most interesting militaria collected from the site and the discussion on their value as archeological evidence.
ill. ; 29 cm
Keywords: arms; armour; medieval; siege; Bolesław III the Generous